The Role of Citizenship Education in Raising Citizenship Awareness - Dadang Mulyana (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
Citizenship awareness is a critical aspect in identity formation and active participation in community life. This research aims to explore and analyze the role of Civic Education (PKn) learning in developing civic awareness among students. This research uses a qualitative approach with descriptive methods. The research results show that learning Citizenship Education (PKn) has a positive impact in forming civic awareness among individuals. Through Civics, students can understand their rights and obligations as citizens, as well as develop skills for active participation in civic life. Apart from that, Civics also helps in instilling important civic values such as mutual cooperation, tolerance, justice, democracy and unity. The results of this research provide a strong basis for the role of Civics in forming individuals who are responsible, aware of their rights and obligations, and ready to contribute to building a better society.